Does Entitlement Card ensure Utilization of Urban Primary Healthcare Clinic in Bangladesh? - Mizan, Sharmin; Rahman, Md Mizanur; Safii, Razitasham binti; Ahmad, Sk Akhtar (Journal of Maternal and Child Health, 2020)
Background: Although Bangladesh substantial